2014
DOI: 10.1021/mp500332m
|View full text |Cite
|
Sign up to set email alerts
|

On the Barrier Properties of the Cornea: A Microscopy Study of the Penetration of Fluorescently Labeled Nanoparticles, Polymers, and Sodium Fluorescein

Abstract: Overcoming the natural defensive barrier functions of the eye remains one of the greatest challenges of ocular drug delivery. Cornea is a chemical and mechanical barrier preventing the passage of any foreign bodies including drugs into the eye, but the factors limiting penetration of permeants and nanoparticulate drug delivery systems through the cornea are still not fully understood. In this study, we investigate these barrier properties of the cornea using thiolated and PEGylated (750 and 5000 Da) nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
105
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(112 citation statements)
references
References 49 publications
5
105
0
2
Order By: Relevance
“…Sodium fluorescein was used as a model dye due to its moderate but easily quantifiable permeability through intact corneal tissue [6, 18]. Hence, a loss in tissue integrity would be readily identifiable with this dye.…”
Section: Methodsmentioning
confidence: 99%
“…Sodium fluorescein was used as a model dye due to its moderate but easily quantifiable permeability through intact corneal tissue [6, 18]. Hence, a loss in tissue integrity would be readily identifiable with this dye.…”
Section: Methodsmentioning
confidence: 99%
“…Of these layers, the epithelium is the major barrier for transcorneal permeation, especially for nanoparticles and larger molecular weight drugs. [19] For example, it has been found that, of the five layers of the cornea, the corneal epithelium is the rate-limiting barrier for most transcorneal permeation, especially water-soluble compounds, whereas the corneal stroma and endothelium are only a significant barrier for small, lipophilic compounds. [20,21] This is due specifically to the suprabasal layer of the cornea that contains tight junctions between cells as well as a high clauden density limiting the passage of even small molecules into the ocular region.…”
Section: Primary Physiological Barriersmentioning
confidence: 99%
“…[15][16][17] Corneal epithelium barrier -The epithelial layer of the cornea is the rate-limiting barrier for most transcorneal penetration. [19][20][21] -Due to the narrow intercellular tight junctions and high claudin density in the superficial layer of the corneal epithelium. [22] Vitreous clearance of drug -Once drugs penetrate into the vitreous body, they can be cleared via two routes: an anterior route and a posterior route.…”
Section: Primary Physiological Barriersmentioning
confidence: 99%
“…Роговица подвержена повышенной опасно-сти, потому что выступает в роли защитно-го барьера для внутренних структур глаза. Она препятствует проникновению не толь-ко инородных тел, но и лекарственных пре-паратов [3,4].…”
Section: работа выполнена при поддержке российского фонда фундаменталunclassified